1985
DOI: 10.1515/znc-1985-7-804
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pH Changes and Elicitor Induced Production of Glyceollin Isomers in Soybean Cotyledons

Abstract: During the incubation of soybean cotyledons with Pmg-elicitor for 22 hours the pH of the diffusion droplets increases from 7.2 to 8.3. This pH-shift is a precondition for the formation of the typical red colour of the diffusion droplet. After inhibiting the pH-shift by the use of 100 mм phosphate or Tris buffer instead of 10 mм buffer as solvent for the elicitor, the red colour is no longer formed with the exeption of 100 mM Ammediol buffer. However, the normal pattern of pterocarpan induction can be measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The pH of diffusion droplets increased from 7.2 to 8.3 after 22 h when soybean cotyledons were incubated with a fungal elicitor. This shift in pH was a precondition for the induced production of glyceollin isomers (17), which might indicate that the change in pH in P. vulgaris is also involved in the initial stages of phytoalexin formation.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The pH of diffusion droplets increased from 7.2 to 8.3 after 22 h when soybean cotyledons were incubated with a fungal elicitor. This shift in pH was a precondition for the induced production of glyceollin isomers (17), which might indicate that the change in pH in P. vulgaris is also involved in the initial stages of phytoalexin formation.…”
Section: Resultsmentioning
confidence: 96%
“…It was suggested that changes in the intracellular pH (17), intracellular phosphate concentrations (24), or the membrane potential (19) tions and pH observed in plant cells after elicitor addition (24). In that study the plant cells were not aerated during the NMR measurements.…”
mentioning
confidence: 96%
“…Rapid changes in cytoplasmic pH have been implicated as a mechanism of signal transduction in a wide variety of biological systems (4,10,13,20,21). Although the occurrence of such pH transitions under physiological conditions has been questioned recently in animal cells (6,9,30), there is still substantial evidence for their occurrence during the defense response in plants (4,13,20,21,27).…”
mentioning
confidence: 99%
“…Although the occurrence of such pH transitions under physiological conditions has been questioned recently in animal cells (6,9,30), there is still substantial evidence for their occurrence during the defense response in plants (4,13,20,21,27). This defense response, as it is currently understood, involves a rather global change in cell biochemistry encompassing transitions in pathways as diverse as phytoalexin synthesis (7), callose formation (5,14), biosynthesis of lignin-like material (5,22), hydroxyproline-rich protein synthesis (5), release of H202 (2), production of hydrolytic enzymes (5,27), synthesis of protease inhibitors (5), and hypersensitive cell death (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation